Neurognathostomiasis in a young child in India: A case report. Issue 5 (October 2015) - Kulkarni, Shilpa; Sayed, Rafat; Garg, Meenal; Patil, Varsha
Abstract: Eosinophilc meningitis is commonly associated with Angiostrongylus and Gnathostoma infection and has largely been reported from Thailand. We present the first case report of neurognathostomaisis in a pediatric patient from India. A 3.5 year old girl presented with fever, parasthesis, behavioral changes followed by flaccid quadriparesis. Neuroimaging showed haemorrhagic radiculomyelitis with cerebrospinal fluid eosinophilia. Diagnosis of Gnathostoma infection was confirmed serologically and she was treated with anthelminthic drugs and steroids. This report emphasizes the increasing importance of central nervous system helminithic infections as an alternative diagnosis to common infections like neurotuberculosis in developing countries, even in pediatric patients. Increasing intercontinental travel and migration have increased the incidence and importance in the developed world as well. Graphical abstract: Highlights: Neurognathostomiasis primarily reported from Thailand First pediatric case from India To be considered as a differential in unexplained CNS infections Need to standardize diagnostic and treatment guidelines